A novel Zn–Al spinel-alumina composite supported gold catalyst for efficient CO oxidation. Issue 80 (14th September 2021) - Ding, Jingyi; Fang, Qiang; Huo, Guodong; Liu, Kuo; Liu, Wei; Zhang, Yaru; Su, Yang; Li, Xuning; Zou, Xuhua; Xu, Xiufeng; Qi, Shixue; Ren, Wanzhong; et al.
Abstract : A spinel-alumina composite supported gold catalyst with excellent CO oxidation activity was developed, and the activation atmosphere could tune the reaction paths and affect its activity by adjusting the amount of surface adsorbed water species. Abstract : A spinel-alumina inert oxide supported gold catalyst with high Au dispersion and excellent CO oxidation activity was developed by a deposition–precipitation method. The activation atmosphere could tune the reaction pathway by adjusting the amount of surface adsorbed water species, thus transforming the reaction intermediates from HCO3 − or CO3 2− to COOH.